Comparison of Preventive and Therapeutic Zinc Supplementation in Young Children in Burkina Faso: A Cluster-Randomized, Community-Based Trial. Issue 10 (3rd August 2016) - Becquey, Elodie; Ouédraogo, Cesaire T; Hess, Sonja Y; Rouamba, Noel; Prince, Lea; Ouédraogo, Jean-Bosco; Vosti, Stephen A; Brown, Kenneth H
Abstract: Background: The WHO and UNICEF recommend therapeutic zinc supplementation (TZS) for the treatment of diarrhea. In zinc-deficient populations, preventive zinc supplementation might provide greater benefits for reducing diarrhea and malaria incidence and increasing growth and plasma zinc (pZn) concentration. If effective, intermittent preventive zinc supplementation (IPZS) would cost less than daily preventive zinc supplementation (DPZS). Objective: We assessed the effects of IPZS, DPZS, and TZS in children on the primary outcomes of diarrhea incidence, malaria incidence, growth, and pZn concentration compared with nonsupplemented control groups. Methods: Rural Burkinabe children ( n = 7641; 6–30 mo old) in 36 clusters were randomly assigned to 1 of 5 treatment groups for 16, 32, or 48 wk: 1 ) IPZS (10 mg Zn/d for 10 d every 16 wk); 2 ) DPZS (7 mg Zn/d); 3 ) TZS (20 mg Zn/d for 10 d for diarrhea); 4 ) morbidity surveillance control (MSC); or 5 ) nonintervention control (NIC). Supplemented groups remained masked until completion of primary analyses with mixed models. Results: At baseline, stunting (28.6%) and low pZn concentration (<65 μg/dL; 43.5%) were common. After 48 wk, mean ± SE pZn increased more ( P = 0.008) in the DPZS group (3.9 ± 1.3 μg/dL) than in the TZS (−0.5 ± 1.2 μg/dL) and NIC (−1.2 ± 0.9 μg/dL) groups. All supplemented groups had a moderately lower incidence of reported diarrhea (0.48–0.49 compared with 0.57 episodes/100 d, P = 0.001) and reported fever (1.1–1.2 compared with 1.5 episodes/100d, P < 0.001) and gained slightly less length (3.15–3.20 compared with 3.36 cm/16 wk, P < 0.001) than the MSC group, but did not differ from each other. Prevalence of diarrhea and incidences of confirmed fever and malaria were not different across study groups. Conclusions: The preventive and TZS groups had reduced diarrhea incidence, but it is uncertain whether this resulted from a functional response to zinc or reporting bias. The comparison should be re-examined in populations known to respond to zinc supplementation. This trial was registered at www.clinicaltrials.gov as NCT00944359.